Why God Had to Have an Immaculate Mother. (10th May 2016) - Epsen, Edward
Abstract: Anselm's argument for the salvific necessity of the Incarnation in his Cur Deus Homo is justly famous and elegantly simple: only man ought; only God can; therefore, only a God‐man both ought and can (atone for sin). Unfortunately it is a paralogism, trading on an equivocal use of 'ought'. It is not difficult, however, to reconceive the meaning of the terms 'ought' and 'can' in a way that both renders the argument formally valid and deepens our christology. Sin may be conceived, per Anselm's own insistence, as a condition of the human soul in its relation to God, a failure of the human will to establish itself in harmonious union with the divine will. If the integrity of created human nature requires that its psychological conditions are propagated together with it, then one who has both the duty and ability to atone for sin must be descended from Adam but must enjoy the original justice of the soul that Adam rejected and deformed in himself. Thus, systematically reconstructing Anselm's argument has the surprising consequence of enabling us to posit an argument for the salvific necessity of the Immaculate Conception as a preparatory stage in the hypostatic union of the Incarnation.